Correlation of gut microbial diversity to sight-threatening diabetic retinopathy - Rehana Khan; Abhishek Sharma; Raghul Ravikumar; Sobha Sivaprasad; Rajiv Raman (BMC Microbiology, 2024)
Abstract Purpose To determine the association of gut microbiome diversity and sight-threatening diabetic retinopathy (STDR) amongst patients with pre-existing diabetes. Methods A cross-sectional study was performed, wherein 54 participants selected in total were placed into cases cohort if diagnosed with STDR and those without STDR but had a diagnosis of diabetes mellitus of at least 10-year duration were taken as controls. Statistical analysis comparing the gut microbial alpha diversity between cases and control groups as well as patients differentiated based on previously hypothesized Bacteroidetes/Firmicutes(B/F) ratio with an optimal cut-off 1.05 to identify patients with STDR were performed. Results Comparing gut microbial alpha diversity did not show any difference between cases and control groups. However, statistically significant difference was noted amongst patients with B/F ratio ≥1.05 when compared to B/F ratio < 1.05; ACE index [Cut-off < 1.05:773.83 ± 362.73; Cut-off > 1.05:728.03 ± 227.37; p-0.016]; Chao1index [Cut-off < 1.05:773.63 ± 361.88; Cut-off > 1.05:728.13 ± 227.58; p-0.016]; Simpson index [Cut-off < 1.05:0.998 ± 0.001; Cut-off > 1.05:0.997 ± 0.001; p-0.006]; Shannon index [Cut-off < 1.05:6.37 ± 0.49; Cut-off > 1.05:6.10 ± 0.43; p-0.003]. Sub-group analysis showed that cases with B/F ratio ≥ 1.05, divided into proliferative diabetic retinopathy (PDR) and clinically significant macular edema (CSME), showed decreased diversity compared to controls (B/F ratio < 1.05). For PDR, all four diversity indices significantly decreased (p < 0.05). However, for CSME, only Shannon and Simpson indices showed significant decrease in diversity (p < 0.05). Conclusions Based on clinical diagnosis, decreasing gut microbial diversity was observed among patients with STDR, although not statistically significant. When utilizing B/F ratio, the decreasing gut microbial diversity in STDR patients seems to be associated due to species richness and evenness in PDR when compared to decreasing species richness in CSME.